Flexibilidade e individualismo – armadilhas neoliberais para a moldagem do ser social - Vieira, Raphael Henrique de Araújo (2023)
The objective of this paper is to analyze, through bibliographic and documental resources, from a Marxist epistemological point of view, the effects of the advance of the categories flexibility and individualism as molds for the social being. We propose that these categories, which are "weapons" of neoliberal thought, are crucial to the understanding of the contemporary individual in the midst of capital's attempts to solve its cyclical crises. As we know, the modern social being is permeated by a lack of social bonds, affected by a notion of collectivity that is not very solid. The values of the being, individualistic and flexible at all times, become those of the market, following a business logic. In this sense, the "antidotes" used by contemporary financial capitalism, guided by the neoliberal doctrine, find echoes in neuralgic areas for social experiences. In a globalized world, interconnected by digital networks, work, education, and communication suffer attacks based on the two characteristics emphasized here. Attacks that provide harmful withdrawals of labor rights, intensify and make even more precarious the daily work, lead to the construction of an uncritical and market-oriented education, and question the values of truth, science, and democracy. In short, the neoliberal antidote, based on flexibility and individualism, is a (harmful) weapon used in various sectors to enhance the profit of a capital that lives in crisis and is always dissatisfied. These are weapons used to alienate and mold the social being in its own way.